edible coating mbote terhadap mutu dan ketahanan buah cabai merah yang diinfeksi jamur Colletotrichum sp. - shelo mitha salma (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
Red chili are widely used for food ingredients, but are prone to post-harvest damage with short shelf life and are susceptible to anthracnose disease. The application of edible coating starch is considered to be able to extend thhe shelf life of thhe fruit and is safe for consumption. Mbote tubers have the possibility to be used as edible coating. This study aims to determine the most effective concentration in maintaining fruit quality against anthracnose disease. This study used a completely randomized design (CRD) with 6 treatments, namely 0%, 1%, 2%, 3%, 4%, 5% and repeated 4 times. The variables in this study are texture, fruit weight loss, incubation period, disease incidence, and disease severity. Data will be analyzed using ANOVA, if there is areal difference, a further test will be conducted at the 5% level. The results showed that application of edible coatng of mbote tubers had no signiificant effect on texture, fruit weight loss, incubation period and disease incidence, but had a significant effect on disease severity with the most effective concentration being the treatment with a concentration of 2%.Keywords: anthracnose, Colletotrichum sp., edible coating, mbote tuber, red chili